Characterisation of two novel bacteriocin-like substances produced by Bacillus amyloliquefaciens ELI149 with broad-spectrum antimicrobial activity. (December 2017) - Salazar, Francisco; Ortiz, Aurelio; Sansinenea, Estibaliz
Graphical abstract: Highlights: Isolation and characterisation of two known lipopeptides (surfactin and fengycin). Fengycin showed marked antifungal activity against phytopathogens, causing cellular damage to several structures. Isolation of two unknown bacteriocins with different broad-spectrum antimicrobial activity. The liquid bacteriocin had more antimicrobial activity than the solid bacteriocin. Purification by silica gel column chromatography was effective to isolate the compounds. Abstract: Objectives: The aim of this study was to isolate and characterise antifungal and bactericidal compounds from Bacillus amyloliquefaciens strain ELI149. Methods: An absorbent resin (Amberlite ® XAD-16) and silica gel column chromatography were used for isolation and purification purposes, respectively. Antibacterial and antifungal assays were performed by the well diffusion method to demonstrate the biological activity of each compound. Cell damage of the tested fungi was evaluated for fengycin under phase-contrast microscopy. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and mass spectroscopy techniques were performed to estimate the approximate molecular mass of each compound. Results: Two bacteriocin-like substances (BLSs) with different physical properties and inhibitory activities were isolated along with two known antifungal compounds. The two BLSs were heat stable and were not sensitive to acid or alkaline conditions (pH 2–10), with broad-spectrum antimicrobial activity. The antifungal compounds were identified as surfactin and fengycin. Only fengycin showed marked antifungal properties against several phytopathogens. Conclusions: The two isolated BLSs were partially characterised and their bactericidal properties were analysed. The antifungals compounds were identified as surfactin and fengycin, this latter being mainly responsible for the antifungal activity.